Letters of the engraver Francesco Maria Gaetano Ghinghi (1689-1762) to Anton Francesco Gori (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
The letters analysed in this article, now in the Biblioteca Marucelliana in Florence, are written from Naples by the famous gem-engraver, Francesco Maria Gaetano Ghinghi (1689-1762) to the renowned scholar and antiquarian Anton Francesco Gori. They give very interesting news about the activity of The Laboratorio delle Pietre Dure in Naples, that began its production in 1738, formed by Ghinghi, the first Director, and the Florentine craftsmen who had come with him. Ghinghi offers informations to reconstitute gems’s circulation in Naples, in that period; relates about antiquities found at Herculaneum (Gori was one of the first writer of those excavations), and about Antonio Pichler in Naples, founder of illustrious gem-engravers’s family, who Ghinghi knew very well, because both worked for the famous collector Philipp von Stosch. One might ask if the Bourbons, jealous of their gems’s collection, were acquainted with Ghinghi sent casts of their intaglios, made by himself, to Gori, interested in the possession of gems unknown.
Keywords: Francesco Maria Gaetano Ghinghi; Anton Francesco Gori; The Laboratorio delle Pietre Dure in Naples; gem impressions; lapis lazuli workshop; Farnese collection; Antonio Pichler; Philipp von Stosch; Felice Gazzola; Herculaneum